WOODY PLANT DIVERSITY AND ABOVEGROUND CARBON STOCKS OF (Shorea roxburghii G. Don) DOMINANT FORESTS IN TAN PHU, DONG NAI PROVINCE - Van Hop, Nguyen; Hong Viet, Le; Quang Bao, Tran; Thi Luong, Nguyen (Journal of Forestry Science and Technology, 2020)
Plant diversity and carbon stocks play an important role in an increasingly complex climate change context. A total of 12 sample plots (50 m x 50 m) were established in 3 three different forest states, 4 plots/each forest state. Together with the quantitative analysis method of biodiversity indicators and the biomass equation (AGB) were used to determine the diversity of woody plants and aboveground carbon stocks of the Shorea roxburghii dominant forests at Tan Phu, Dong Nai. The results showed that a total of 92 woody plant species, 65 genera of 40 families were recorded. Of them, 37 threatened species were found in the IUCN list (2020), 6 species in the Vietnamese Red Data Book (2007), and 3 species in Decree No. 06 of the Government. The quantitative indicators of biodiversity were identified: Important value index (IVI) from 45.3-57.6%; Similarity index (Sc) from 66-74%; Margalef (d) from 6.7-7.1; Pielou (J') from 0.80-0.86; Shannon-Wiener (H') from 2.87-3.05; Gini-Simpson (1- λ') from 0.90-0.93; Whittaker (β) from 2.64-2.71; and Rényi index, showed that moderate diversity. A total biomass and average aboveground carbon stocks of the states ranged from 106.15 (t/ha) and 53.07 (tC/ha) to 282.63 (t/ha) and 141.32 (tC/ha). The study clarifies the biodiversity and aboveground carbon storage capacity of the Shorea roxburghii dominant forest in Tan Phu, making an important contribution to climate change mitigation.